Scientific production on COVID-19 in Cuban medical journals during the first 90 days after the start of the pandemic - Roberto Zayas Mujica; Soraya Madero Durán; Beatriz Rodríguez Alonso; José Enrique Alfonso Manzanet (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: Since the first case of SARS-CoV-2 was confirmed, the pandemic has experienced an almost uncontrollable increase in the number of cases.  The scientific production plays a key role in the fight against the necessary control and eradication of the pandemic.  From the very beginning, thousands of articles per day are produced at international level; furthermore, editorials and databases have made a great effort to give due priority and visibility to these contributions.  Cuba has made significant efforts in this respect. Objective: To characterize the scientific production on COVID-19 in Cuban medical journals during the first ninety days after the start of the pandemic in Cuba. Material and Methods: A cross-sectional descriptive study aimed at analyzing 100% of the scientific medical journals was conducted.  Variables such as documental typology, institutional and collaborative affiliations, subject matter, country and time of publication, among others were identified. Results:  In total, 58 % of the articles were published in medical journals and 31,1 % was a contribution by Medisur Journal, University of Medical Sciences in Cienfuegos.  In addition, 77,8 % of the articles were written by Cuban health researchers, 22,6 % of the articles were Letters to the Editor and 20,8 % were original articles. Conclusions: Over the period studied, the national scientific production in Cuban medical journals is low taking into account that the Letters to the Editor are not actual research articles.  Some subject areas in Medical Sciences such as Family Medicine, which could have contributed with their experiences in research work within the community, have not produced any scientific article during this period of time.